UNIFIKASI DALAM PLURALISME HUKUM TANAH DI INDONESIA (REKONSTRUKSI KONSEP UNIFIKASI DALAM UUPA) - BAKRI, MUHAMMAD (Kertha Patrika; Vol 33 No 1 (2008)DO - 10.24843/KP.2008.v33.i01.p07)
After the enforcement of The Basic Agrarian Law, land law in Indonesia has the character of unification, meaning that only one land law applied that is national land law. Enforcing one particular land law at various society as in Indonesia, can generate injustice. Therefore, the Decision Of People Consultative Assembly Number of IX/MPR/2001 Section 4 letter c opens the opportunity of pluralism in unification sounding: Respecting law supremacy by accommodating varieties in law unification. What is meant by " varieties in law unification" is not clarified.According to the writer, the meaning of varietiesin unification specially land law is : enforcing adjacently two peripheral laws that is, national land law applied all over Indonesia regions and local adat land law. In areas having customary rights, adat law is fully applied adat law, but in areas without customary rights, national land law is use instead.
Keywords: unification, law pluralism